The Influence of Problem-Based Learning Model Assisted by Interactive Multimedia Google Sites on Critical and Creative Thinking Skills in Elementary School - Galih Yoga Pradana; Rif'at Shafwatul Anam; Neni Mariana; Ika Tri Yunianika (UIN Siber Syekh Nurjati Cirebon, 2024)
AbstractThis study aims to (1) assess the significant impact of the Problem-Based Learning (PBL) model, enhanced by Google Sites interactive multimedia, on the critical thinking abilities of fifth-grade elementary students, (2) evaluate the significant effect of the PBL model, supported by Google Sites interactive multimedia, on the creative thinking skills of these students, and (3) examine the combined influence of the PBL model, aided by Google Sites interactive multimedia, on both critical and creative thinking skills of fifth-grade students. This quasi-experimental research utilized a nonequivalent control group design, involving fifth-grade students divided into a control group and an experimental group, each consisting of 30 students. Data analysis was conducted using independent sample t-tests and MANOVA tests. The hypothesis testing results indicate that (1) the PBL model with Google Sites interactive multimedia significantly enhances critical thinking skills, (2) it significantly boosts creative thinking skills, and (3) it has a simultaneous positive effect on both critical and creative thinking skills of fifth-grade students. Future learning is encouraged to develop more diverse educational games to further motivate student learning.Keywords: problem-based learning, interactive multimedia, google sites, critical and creative thinking.AbstrakPenelitian ini bertujuan untuk (1) mengkaji dampak signifikan model Problem-Based Learning (PBL) yang disempurnakan dengan multimedia interaktif Google Sites terhadap kemampuan berpikir kritis siswa sekolah dasar kelas lima, (2) mengevaluasi dampak signifikan model PBL yang didukung oleh multimedia interaktif Google Sites terhadap keterampilan berpikir kreatif siswa tersebut, dan (3) menguji pengaruh gabungan model PBL yang dibantu oleh multimedia interaktif Google Sites terhadap keterampilan berpikir kritis dan kreatif siswa kelas lima. Penelitian kuasi eksperimen ini menggunakan desain kelompok kontrol non-ekuivalen, yang melibatkan siswa kelas lima yang dibagi menjadi kelompok kontrol dan kelompok eksperimen, yang masing-masing terdiri dari 30 siswa. Analisis data dilakukan dengan menggunakan uji-t sampel independen dan uji MANOVA. Hasil pengujian hipotesis menunjukkan bahwa (1) model PBL dengan multimedia interaktif Google Sites secara signifikan meningkatkan keterampilan berpikir kritis, (2) secara signifikan meningkatkan keterampilan berpikir kreatif, dan (3) secara simultan memiliki efek positif terhadap keterampilan berpikir kritis dan kreatif siswa kelas lima. Pembelajaran di masa depan didorong untuk mengembangkan permainan edukatif yang lebih beragam untuk lebih memotivasi pembelajaran siswa.Kata kunci: pembelajaran berbasis masalah, multimedia interaktif, situs google, berpikir kritis dan kreatif.